Quality Management System in Stavropol Research Anti-Plague Institute - O. I. Kogotkova; P. B. Novakov; A. A. Zuenko; L. V. Lyapustina; T. M. Gridina; T. I. Egshatyan; A. N. Kulichenko (Проблемы особо опасных инфекций, 2012)
The analysis of the structure of quality management system and the areas of its activity is presented. Trends for its further improvement are defined.